Publisher Correction: Stem cells: The reprogramming method matters. (January 2018) - Allison, Thomas; Lowry, William
In the version of this News and Views article originally published, an erroneous hyphen was included in the term 'human-induced pluripotent stem cells'; it should have read 'human induced pluripotent stem cells'. This error has now been corrected in all versions of the News and Views article.